Health related quality of life and its associated factors among community-dwelling older people in Sri Lanka: A cross-sectional study - Damayanthi, Hewaratne Dassanayakege Wimala Thushari; Moy, Foong Ming; Abdullah, Khatijah Lim; Dharmaratne, Samath Dhamminda (Elsevier, 2018)
Background: Population ageing has become a public health issue as it is associated with increased morbidity, institutionalization and death. These may directly affect health-related quality of life (HRQOL) of older people. Purpose: The aim of the study was to investigate HRQOL and its associated factors among community-dwelling older people in Kandy district, Sri Lanka. Method: This cross-sectional survey involved 1300 older people. The Euro 5D-3L, International Physical Activity Questionnaire, body mass index, handgrip strength were used to measure HRQOL, physical activity and nutritional status of older people respectively. Factors associated with health-related quality of life were identified through complex sample logistic regression analysis. Results: Majority of older people (81.9%) reported poor health-related quality of life. Middle old (aOR: 12.06, 95% CI: 5.76, 25.23), very old (aOR: 174.74, 95% CI: 39.74, 768.38), vegetarian diets (aOR: 2.13, 95% CI: 1.14, 3.96), under-nutrition (aOR: 3.41, 95% CI: 1.65, 7.04) and over-nutrition (aOR: 1.85, 95% CI: 1.04, 3.28) were significantly associated with poor HRQOL. Using dentures (aOR: 0.05, 95% CI: 0.28, 0.90) was found as a protective factor for poor HRQOL. Conclusions: HRQOL was poor among community-dwelling older people in Kandy district. Nutrition-related factors need to be further investigated to improve HRQOL among older people.